Analisis Pengaruh Literasi Keuangan Syariah dan Keuangan Konvensional terhadap PDB di Masa Pandemic Covid-19 - Al-Aziz, Moh Sofwan Katsir (Jurnal Magister Ekonomi Syariah, 2022)
The aim is to find out how the influence of small business loans, operational costs, the Jakarta Islamic index, and covid 19 on economic growth. The methodology used in this research is descriptive quantitative analysis. The data used were obtained from OJK and BPS. The findings of the test results show that the business credit variable has a high level of significance and the data used is normally distributed. Practical implications in this research can be used as a form of government benchmark to maintain economic stability. Originality in this study was carried out using a multiple linear analysis model by looking at the influence between variables. The results of the tests carried out resulted in all variables having a significant effect.